ANALYZING TECHNOLOGY INTEGRATION IN ENGLISH FOR SPECIFIC PURPOSES (ESP) LEARNING THROUGH A SYSTEMATIC LITERATURE REVIEW OF PRISMA AND SINTA-ACCREDITED JOURNALS - Anwari, Hamdan; Nindyah Pratiwi (Journal of Innovation Research and Knowledge, 2025)
In Indonesia, educational research has focused mostly on including technology into English for Specific Purposes (ESP) learning. This study systematically reviews ESP research published in SINTA-accredited journals (Ranks 1 and 2) applying PRISMA methodology to guarantee rigor and transparency. Examining 45 papers overall, focusing toward significant trends in research design, participant demographics, applied technique, and technological advancements, With considerable application of tools like digital storytelling, Prezi, and multimedia platforms to promote language acquisition, the review reveals a clear inclination for qualitative and quantitative approaches. Among university students, engineering, Islamic education, and maritime studies are the most often sought-after disciplines. Among routinely utilized tools include pre/post exams, reflective journals, and questionnaires. The results show that learners' domain-specific vocabulary, communication skills, and general motivation enhance with technology-infused ESP instruction. Though there are encouraging patterns, a sizable portion of the study is still non-interventionist, suggesting the necessity of more practical and development-oriented studies. The study underlines the transforming ability of technology in creating more specialized, dynamic, and interesting ESP learning settings. Particularly in vocational and professional learning environments, future research should investigate more deeply the cognitive and pedagogical ramifications of developing technologies including artificial intelligence, virtual reality, and adaptive learning systems.